Forming Student's Saving Behaviour through Financial Literacy, Parental Financial Education, and Self Control - Suwatno, Suwatno; Waspada, Ikaputera; Mulyani, Heni (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2021)
Saving behaviour is highly dependent on the surrounding environment. The current behaviour of saving at this time will carry over to their lives in the future. In the era of globalization and technological developments in finance or what is often referred to as financial technology (fintech), it is very difficult for someone to distinguish between needs and wants. This study aims to analyse the factors that influence students' saving behaviour in terms of financial literacy, parental financial education, and self-control. The research method used a quantitative design with an ex post facto approach through path analysis techniques. The research data collection technique used a questionnaire. The population and research sample were students of Vocational High Schools in West Java. Determination of the number of samples using the purposive sampling method. The results showed that financial literacy significantly affected self-control (Sig. ≤ 0.05), financial education from parents significantly affected self-control (Sig. ≤ 0.05), financial literacy significantly affected saving behaviour (Sig. ≤ 0.05), financial education from parents significantly influences saving behaviour (Sig. ≤ 0.05), and self-control significantly influences saving behaviour (Sig. ≤ 0.05). This shows that to form student saving behaviour, financial literacy, self-control, and financial education from parents are needed.